Effectiveness of simulation-based nursing education depending on fidelity: a meta-analysis. Issue 1 (December 2016) - Kim, Junghee; Park, Jin-Hwa; Shin, Sujin
Abstract Background Simulation-based nursing education is an increasingly popular pedagogical approach. It provides students with opportunities to practice their clinical and decision-making skills through various real-life situational experiences. However, simulation approaches fall along a continuum ranging from low-fidelity to high-fidelity simulation. The purpose of this study was to determine the effect size of simulation-based educational interventions in nursing and compare effect sizes according to the fidelity level of the simulators through a meta-analysis. Method This study explores the quantitative evidence published in the electronic databases EBSCO, Medline, ScienceDirect, ERIC, RISS, and the National Assembly Library of Korea database. Using a search strategy including the search terms "nursing, " "simulation, " "human patient, " and "simulator, " we identified 2279 potentially relevant articles. Forty studies met the inclusion criteria and were retained in the analysis. Results This meta-analysis showed that simulation-based nursing education was effective in various learning domains, with a pooled random-effects standardized mean difference of 0.70. Subgroup analysis revealed that effect sizes were larger for high-fidelity simulation (0.86), medium-fidelity simulation (1.03), and standardized patients (0.86) than they were for low-fidelity and hybrid simulations. In terms of cognitive outcomes, the effect size was the largest for high-fidelity simulation (0.50). Regarding affective outcome, high-fidelity simulation (0.80) and standardized patients (0.73) had the largest effect sizes. Conclusions These results suggest that simulation-based nursing educational interventions have strong educational effects, with particularly large effects in the psychomotor domain. Since the effect is not proportional to fidelity level, it is important to use a variety of educational interventions to meet all of the educational goals.